2013
DOI: 10.1002/ajh.23374
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lenalidomide in POEMS syndrome: A retrospective study of 20 patients

Abstract: POEMS syndrome is a rare disorder characterized by polyneuropathy, monoclonal gammopathy, multiorgan involvement, and elevated vascular endothelial growth factor levels. Localized bone lesions require irradiation, whereas young patients with disseminated disease receive intensive treatment with stem cell support. Treatment of older and non responding patients is not yet standardized. We report the use of a combination of lenalidomide and dexamethasone in 20 patients with POEMS syndrome. Four patients were newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 22 publications
9
39
0
Order By: Relevance
“…Although follow-up is short, the authors report that several patients had rapid neurological response, no patient has died, and one patient has progressed. These results are similar to previous case reports and case series [168,169,178] though relapses have been reported. In the largest case series of 20 patients [169], all patients responded, but 4 patients relapsed 3-10 months after the end of treatment.…”
Section: Management Of Poems Syndrome With Disseminated Bone Marrow Isupporting
confidence: 93%
See 1 more Smart Citation
“…Although follow-up is short, the authors report that several patients had rapid neurological response, no patient has died, and one patient has progressed. These results are similar to previous case reports and case series [168,169,178] though relapses have been reported. In the largest case series of 20 patients [169], all patients responded, but 4 patients relapsed 3-10 months after the end of treatment.…”
Section: Management Of Poems Syndrome With Disseminated Bone Marrow Isupporting
confidence: 93%
“…These results are similar to previous case reports and case series [168,169,178] though relapses have been reported. In the largest case series of 20 patients [169], all patients responded, but 4 patients relapsed 3-10 months after the end of treatment. Three of these treatment failures responded to further therapy, including one who responded to reintroduction of the lenalidomide-dexamethasone combination.…”
Section: Management Of Poems Syndrome With Disseminated Bone Marrow Isupporting
confidence: 93%
“…1 Due to the rarity of the disease, prospective therapeutic clinical trials are rare. 2,3 Based on experience with patients with solitary plasmacytomas of bone (SPB), the approach for patients with POEMS, negative bone marrows, and limited bone lesions has been targeted irradiation for patients with 1 to 3 isolated bone lesions. 4 Anecdotal reports have shown benefit, [5][6][7][8][9][10] but there are no published data on long-term results or time to treatment failure with this approach.…”
Section: Introductionmentioning
confidence: 99%
“…11 More recently, two studies have demonstrated promising results in the phase II trial setting with favorable outcomes. [12][13][14] As with MM, the use of HDT/ASCT in patients with POEMS has yielded encouraging results, though most reported series are small and single center experiences. [15][16][17][18][19][20] We, therefore, sought to characterize the effect of ASCT as therapy for patients with POEMS syndrome, determining the effect on organ-specific dysfunction and delineating key patient-and disease-specific factors predicting for outcome.…”
Section: Introductionmentioning
confidence: 99%